Нерезонансный фон в изобарных моделях фоторождения η-мезонов на нуклонах; Известия вузов. Физика; Т. 59, № 3 - Трясучев В. А. Владимир Андреевич; Алексеев Б. А. Борис Александрович; Яковлева В. С. Валентина Станиславовна; Кондратьева А. Г. Алла Георгиевна (2016, 2016)
Заглавие с экрана